Electrolyte solution, electrochemical device, and electronic apparatus
By using additives containing nitrogen-containing heterocyclic anhydrides and borate ester compounds in the electrolyte of lithium-ion batteries, combined with the surface density of the adapted positive electrode material layer and negative electrode material layer, the problem of deterioration of the high-temperature performance of lithium-ion batteries under high voltage is solved, and the battery's high-temperature circulation performance is improved.
Patent Information
- Application Number
- CN202411942574.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-24
AI Technical Summary
At high voltage, the high-temperature performance of lithium-ion batteries deteriorates, resulting in the inability to guarantee the cycle life. Excessive amount of existing high-temperature additives will lead to an increase in film formation impedance, limiting its application.
By using nitrogen-containing heterocyclic anhydride compounds and borate ester compounds as the first and second additives in the electrolyte, and the amount of them is matched with the surface density of the positive electrode material layer and the negative electrode material layer, the amount of the widening high-temperature additive is achieved and the high-temperature cycling performance of the battery is improved.
By balancing the amount of additives with the surface density of the positive electrode material layer and the negative electrode material layer, the positive and negative electrode materials are effectively protected, the high-temperature cycling performance of the battery is improved, and the performance deterioration caused by increased impedance is avoided.
Smart Images

Figure CN119742453A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to electrolytes, electrochemical devices and electronic devices. Background Art
[0002] Lithium-ion batteries are widely used in 3C digital, power tools, aerospace, energy storage, power vehicles and other fields due to their high specific energy, no memory effect, long cycle life and other advantages. The rapid development of electronic information technology and consumer products has put forward higher requirements for high voltage and high energy density of lithium-ion batteries. In lithium-ion batteries, high-voltage positive electrode materials are widely used in portable electronic devices such as mobile phones and laptops, as well as electric vehicles and large energy storage devices due to their high energy density, environmental friendliness and long cycle life.
[0003] However, as the limiting voltage of the positive electrode material continues to increase (especially 4.3V+), under high voltage, the high-temperature performance of the battery will seriously deteriorate due to the oxidation of the electrolyte on the positive electrode side, or the dissolution of transition metals on the negative electrode side will destroy the SEI film, and long cycle life cannot be guaranteed.
[0004] In the related art, in order to improve the high-temperature performance of lithium-ion batteries under high energy density, different types of high-temperature additives are usually introduced into the electrolyte, such as sulfonates, anhydrides, carbonates, etc. However, excessive addition of these additives will lead to too large film formation impedance, deteriorating the high-temperature cycle performance of the battery, thereby limiting the application of high-temperature additives.
[0005] Therefore, how to expand the application of high-temperature additives and further improve the high-temperature cycle performance of batteries has become an urgent problem to be solved. Summary of the invention
[0006] In order to solve or partially solve the problems existing in the related art, the present application provides an electrolyte, an electrochemical device and an electronic device, which can be used in combination with a second additive and a first additive, and the content of the additive is adapted to the surface density of the positive electrode material layer and the negative electrode material layer, so as to achieve the effect of expanding the usage of the first additive and further improving the high temperature cycle performance of the battery.
[0007] In a first aspect, the present application provides an electrolyte, including a first additive and a second additive, wherein the first additive includes a nitrogen-containing heterocyclic acid anhydride compound, and the second additive includes a borate compound, and the first additive and the second additive satisfy the following relationship with the positive and negative electrode material layers:
[0008] 105≤(Ya+Yb) / (M*N)≤2000
[0009] The mass percentage of the first additive in the electrolyte is Ya%, the mass percentage of the second additive in the electrolyte is Yb%, and the mass of the positive electrode material layer per unit area on the positive electrode sheet is M g / cm 2 , the mass of the negative electrode material layer per unit area on the negative electrode sheet is N g / cm 2 .
[0010] As an optional embodiment, the first additive and the second additive satisfy the following relationship with the positive and negative electrode material layers:
[0011] 200≤(Ya+Yb) / (M*N)≤1000.
[0012] As an optional embodiment, the structural formula of the nitrogen-containing heterocyclic acid anhydride compound is as follows:
[0013]
[0014] In Formula 1, X1 is one of C and N atoms, X2 is a N atom, and R1 and R2 are each independently selected from a benzene ring, a cyano group, a halogen atom, a hydrogen atom, a C1-C10 alkyl group, a C1-C10 unsaturated alkyl group, a C1-C10 halogenated alkyl group, and a C1-C10 halogenated unsaturated alkyl group; preferably, R1 and R2 are each independently selected from a benzene ring, a cyano group, a halogen atom, a hydrogen atom, a C1-C3 alkyl group, a C1-C3 unsaturated alkyl group, a C1-C3 fluorinated alkyl group, and a C1-C10 fluorinated unsaturated alkyl group.
[0015] As an optional embodiment, the first additive comprises at least one of the following nitrogen-containing heterocyclic acid anhydride compounds:
[0016]
[0017]
[0018] As an optional embodiment, the structural formula of the borate ester compound is as follows:
[0019]
[0020] In formula 2, R3, R4, and R5 are each independently selected from one of a C1-C10 alkyl group, a C1-C10 unsaturated alkyl group, a C1-C10 fully halogenated or partially halogenated alkyl group, and a C1-C10 fully halogenated or partially halogenated unsaturated alkyl group; preferably, R3, R4, and R5 are each independently selected from one of a C1-C5 fully fluorinated or partially fluorinated alkyl group, and a C1-C5 fully fluorinated or partially fluorinated unsaturated alkyl group.
[0021] As an optional embodiment, the second additive comprises at least one of the following borate compounds:
[0022]
[0023]
[0024]
[0025] As an optional embodiment, 0.01≤Ya≤10; and / or, 0.01≤Yb≤5; and / or, 0.035≤M≤0.15; and / or, 0.025≤N≤0.12.
[0026] As an optional embodiment, 1≤Ya≤8; and / or, 0.5≤Yb≤3.
[0027] A second aspect of the present application provides an electrochemical device, comprising a positive electrode sheet, a negative electrode sheet, a separator, and the aforementioned electrolyte.
[0028] As an optional embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active slurry layer located on at least one side of the positive electrode current collector, and the positive electrode active slurry layer includes a positive electrode active material.
[0029] Preferably, the positive electrode active material is selected from one or more of lithium cobalt oxide LiCoO2, lithium nickel manganese cobalt ternary material, lithium iron phosphate LiFePO4, and lithium manganese oxide LiMn2O4.
[0030] Further preferably, the positive electrode active material is selected from lithium nickel manganese cobalt ternary materials.
[0031] A third aspect of the present application provides an electronic device, comprising the electrochemical device described above.
[0032] The technical solution provided by this application may have the following beneficial effects:
[0033] The inventor of the present application has found through research that the amount of the first additive and the second additive is related to the surface density of the positive electrode material layer and the negative electrode material layer in the positive and negative electrodes. The greater the surface density of the positive electrode material layer and the negative electrode material layer in the positive and negative electrodes, the more the amount of the first additive and the second additive is required. However, if the amount of the first additive and the second additive is too small and does not match the surface density of the positive electrode material layer and the negative electrode material layer in the positive and negative electrodes, then it will not play an effective role and will not effectively protect the positive and negative electrode materials; conversely, if the amount of the first additive and the second additive is too large, it will cause the impedance in the system to increase and the cycle performance to deteriorate. Therefore, it is necessary to balance the amount of the first additive and the second additive with the surface density of the positive electrode material layer and the negative electrode material layer, so that the amount of the first additive and the second additive is compatible with the surface density of the positive electrode material layer and the negative electrode material layer, so as to achieve effective protection of the positive and negative electrodes and improve the high temperature cycle performance of the battery.
[0034] Research has found that when the amount of the first additive and the second additive and the surface density of the positive electrode material layer and the negative electrode material layer satisfy 105≤(Ya+Yb) / (M*N)≤2000, the amount of the first additive and the second additive can be balanced with the surface density of the positive electrode material layer and the negative electrode material layer, so that the amount of the first additive and the second additive is adapted to the surface density of the positive electrode material layer and the negative electrode material layer, so as to achieve effective protection of the positive and negative electrodes and improve the high temperature cycle performance of the battery.
[0035] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.
[0037] Figure 1 1 is a graph showing the EIS test results of the battery shown in the embodiment of the present application. DETAILED DESCRIPTION
[0038] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0039] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0040] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0041] In the related art, in order to improve the high-temperature performance of lithium-ion batteries under high energy density, different types of high-temperature additives are usually introduced into the electrolyte, such as sulfonates, anhydrides, carbonates, etc. However, excessive addition of these additives will lead to too large film formation impedance, deteriorating the high-temperature cycle performance of the battery, thereby limiting the application of high-temperature additives.
[0042] In response to the above problems, an embodiment of the present application provides an electrolyte that can be used in combination with a second additive and a first additive, and the content of the additive is adapted to the surface density of the positive electrode material layer and the negative electrode material layer, so as to achieve the effect of expanding the usage of the first additive and further improving the high temperature cycle performance of the battery.
[0043] The present application embodiment provides an electrolyte, including a first additive and a second additive, wherein the first additive includes a nitrogen-containing heterocyclic acid anhydride compound, and the second additive includes a borate compound, and the first additive and the second additive satisfy the following relationship with the positive and negative electrode material layers:
[0044] 105≤(Ya+Yb) / (M*N)≤2000
[0045] The mass percentage of the first additive in the electrolyte is Ya%, the mass percentage of the second additive in the electrolyte is Yb%, and the mass of the positive electrode material layer per unit area on the positive electrode sheet is M g / cm 2 , the mass of the negative electrode material layer per unit area on the negative electrode sheet is N g / cm 2 .
[0046] In the embodiment of the present application, the mass of the positive electrode material layer per unit area on the positive electrode sheet refers to the surface density of the positive electrode material layer, which is M g / cm 2 The mass of the negative electrode material layer per unit area on the negative electrode sheet refers to the surface density of the negative electrode material layer, which is N g / cm 2 .
[0047] In the embodiment of the present application, the first additive includes a nitrogen-containing heterocyclic acid anhydride compound, and the nitrogen-containing heterocyclic acid anhydride compound has an anhydride group and a nitrogen-containing heterocyclic structure, wherein the anhydride group is easy to undergo a hydrolysis reaction with water, because the carbonyl group in the anhydride group has a strong electrophilicity and is easily attacked by the nucleophilic attack of water, and the lone pair of electrons on the oxygen atom of water attacks the carbonyl carbon of the anhydride to form a tetrahedral intermediate, followed by the breaking and recombination of chemical bonds to generate carboxylic acid and acid derivatives, thereby achieving the purpose of removing water; and the nitrogen-containing heterocyclic structure belongs to a Lewis base, and the N atom contained therein belongs to an electron-deficient group, which can be combined with a trace amount of HF in the electrolyte after the ring is opened, thereby achieving the effect of reducing the content of HF in the system. Therefore, the first additive in the embodiment of the present application can efficiently remove trace moisture in the electrolyte, and can reduce the content of HF in the system, and prevent excessive HF content from damaging the electrode material.
[0048] At the same time, the first additive can also participate in film formation at the positive and negative electrodes, stabilize the interface between the positive and negative electrodes, effectively reduce damage to the positive electrode CEI and the negative electrode SEI, and improve the high temperature performance of the battery. This is because the lone pair of electrons of the N atom in the nitrogen-containing heterocyclic structure contained in the first additive produces an electrostatic adsorption effect with the negative charge on the electrode surface, laying the foundation for the subsequent film formation process; secondly, in the process of the first formation, the carbon-nitrogen double bond of the nitrogen-containing heterocyclic structure easily accepts electrons on the negative electrode surface to undergo a reduction reaction to form an SEI film, and can also polymerize on the positive electrode surface, and undergo an oxidation reaction to participate in the formation of the CEI film. In addition, the anhydride group contained in the first additive will be reduced to form an SEI film when the negative electrode is at a low potential, and oxidized to form a CEI film at the positive electrode. However, excessive use of the first additive will result in too large a film formation impedance, which will deteriorate the high temperature cycle performance of the battery.
[0049] The second additive includes borate compounds, which are conducive to the formation of an SEI protective layer containing BO-based compounds on the surface of the negative electrode. The SEI layer containing BO-based compounds can effectively alleviate the oxidation and gas production of Ni in the lithium-nickel-manganese-cobalt ternary material on the electrolyte. In addition, borate compounds can also form a uniform and thin CEI layer on the positive electrode side, forming a CEI protective layer containing BO-based compounds, which can effectively reduce the dissolution of transition metal ions in other positive electrode active materials such as lithium cobalt oxide LiCoO2, lithium ferrous phosphate LiFePO4, and lithium manganese oxide LiMn2O4. The use of the second additive and the first additive can jointly improve the stability of the battery cycle process. At the same time, it can also prevent the first additive from generating excessive impedance, and can further broaden the dosage range of the first additive, thereby further improving the high-temperature cycle performance of the battery.
[0050] The inventor of the present application has found through research that the amount of the first additive and the second additive is related to the surface density of the positive electrode material layer and the negative electrode material layer in the positive and negative electrodes. The greater the surface density of the positive electrode material layer and the negative electrode material layer in the positive and negative electrodes, the more the amount of the first additive and the second additive is required. However, if the amount of the first additive and the second additive is too small and does not match the surface density of the positive electrode material layer and the negative electrode material layer in the positive and negative electrodes, then it will not play an effective role and will not effectively protect the positive and negative electrode materials; conversely, if the amount of the first additive and the second additive is too large, it will cause the impedance in the system to increase and the cycle performance to deteriorate. Therefore, it is necessary to balance the amount of the first additive and the second additive with the surface density of the positive electrode material layer and the negative electrode material layer, so that the amount of the first additive and the second additive is compatible with the surface density of the positive electrode material layer and the negative electrode material layer, so as to achieve effective protection of the positive and negative electrodes and improve the high temperature cycle performance of the battery.
[0051] The study found that when the amount of the first additive and the second additive and the surface density of the positive electrode material layer and the negative electrode material layer satisfy 105≤(Ya+Yb) / (M*N)≤2000, the amount of the first additive and the second additive can be balanced with the surface density of the positive electrode material layer and the negative electrode material layer, so that the amount of the first additive and the second additive is adapted to the surface density of the positive electrode material layer and the negative electrode material layer, so as to achieve effective protection of the positive and negative electrodes and improve the high temperature cycle performance of the battery.
[0052] As an optional embodiment, the first additive and the second additive satisfy the following relationship with the positive and negative electrode material layers:
[0053] 200≤(Ya+Yb) / (M*N)≤1000.
[0054] Further research found that when the amount of the first additive and the second additive and the surface density of the positive electrode material layer and the negative electrode material layer satisfy 200≤(Ya+Yb) / (M*N)≤1000, the amount of the first additive and the second additive can be more effectively balanced with the surface density of the positive electrode material layer and the negative electrode material layer, so that the amount of the first additive and the second additive is more compatible with the surface density of the positive electrode material layer and the negative electrode material layer, so as to achieve more effective protection of the positive and negative electrodes and further improve the high temperature cycle performance of the battery.
[0055] As an optional embodiment, the structural formula of the nitrogen-containing heterocyclic acid anhydride compound is as follows:
[0056]
[0057]
[0058] In Formula 1, X1 is one of C and N atoms, X2 is a N atom, and R1 and R2 are each independently selected from a benzene ring, a cyano group, a halogen atom, a hydrogen atom, a C1-C10 alkyl group, a C1-C10 unsaturated alkyl group, a C1-C10 halogenated alkyl group, and a C1-C10 halogenated unsaturated alkyl group.
[0059] Preferably, X1 is one of C and N atoms, X2 is a N atom, and R1 and R2 are each independently selected from a benzene ring, a cyano group, a halogen atom, a hydrogen atom, a C1-C3 alkyl group, a C1-C3 unsaturated alkyl group, a C1-C3 fluorinated alkyl group, and a C1-C10 fluorinated unsaturated alkyl group.
[0060] As a preferred embodiment, the first additive comprises at least one of the following nitrogen-containing heterocyclic acid anhydride compounds:
[0061]
[0062]
[0063] In the embodiments of the present application, the fluorinated alkane substituents contained in compound 1-2 can form a SEI film containing LiF, improve the stability of SEI and reduce the impedance of film formation; the benzene ring substituents contained in compound 1-3 can improve the oxidation resistance of the electrolyte and enhance the overcharge performance of the battery; the cyano substituents contained in compound 1-5 can remove acid and water, further stabilize the positive electrode material, and improve the stability of the positive electrode side; the alkyl substituents contained in compound 1-4, compound 1-7 and compound 1-8 can increase the solubility of the additive, reduce the viscosity of the additive, and improve the ion mobility.
[0064] As an optional embodiment, the structural formula of the borate ester compound is as follows:
[0065]
[0066] In Formula 2, R3, R4, and R5 are each independently selected from one of a C1-C10 alkyl group, a C1-C10 unsaturated alkyl group, a C1-C10 fully halogenated or partially halogenated alkyl group, and a C1-C10 fully halogenated or partially halogenated unsaturated alkyl group.
[0067] Preferably, R3, R4 and R5 are each independently selected from one of a C1-C5 perfluorinated or partially fluorinated alkyl group and a C1-C5 perfluorinated or partially fluorinated unsaturated alkyl group.
[0068] The borate compound included in the second additive of the embodiment of the present application contains fluorine atoms, which is conducive to forming an SEI protective layer including a BF-based compound and a LiF compound on the surface of the negative electrode. The SEI layer including these two compounds can further effectively inhibit the decomposition of the electrolyte. In addition, the borate compound can also form a uniform and thin CEI layer on the positive electrode side, forming a CEI protective layer including a BF-based compound, which can further effectively reduce the dissolution of transition metal ions.
[0069] As a preferred embodiment, the second additive comprises at least one of the following borate compounds:
[0070]
[0071]
[0072]
[0073] The borate compound selected as the second additive in the embodiment of the present application contains a perfluoroalkane group or a partially fluoroalkane group, which is conducive to forming an SEI protective layer containing a BF-based compound and a LiF compound on the surface of the negative electrode. The SEI layer containing these two compounds can further effectively inhibit the decomposition of the electrolyte. In addition, the borate compound can also form a uniform and thin CEI layer on the positive electrode side, forming a CEI protective layer containing a BF-based compound, which can further effectively reduce the dissolution of transition metal ions.
[0074] As an optional embodiment, 0.01≤Ya≤10.
[0075] In the embodiments of the present application, Ya can be 0.01, 0.3, 0.5, 1, 2, 5, 8, 10 or any value within the above range, and the present application does not limit this.
[0076] Furthermore, 1≤Ya≤8.
[0077] In the embodiments of the present application, Ya can be 1, 2, 5, 8 or any value within the above range, and the present application does not limit this.
[0078] As an optional embodiment, 0.01≤Yb≤5.
[0079] In the embodiments of the present application, Yb can be 0.01, 0.3, 0.5, 1, 2, 3, 5 or any value within the above range, and the present application does not limit this.
[0080] Furthermore, 0.5≤Yb≤3.
[0081] In the embodiments of the present application, Yb can be 0.5, 1, 2, 3 or any value within the above range, and the present application does not limit this.
[0082] As an optional embodiment, 0.035≤M≤0.15.
[0083] In the embodiments of the present application, M can be 0.035, 0.11, 0.15 or any value within the above range, and is not limited in the present application.
[0084] As an optional embodiment, 0.025≤N≤0.12.
[0085] In the embodiments of the present application, N may be 0.025, 0.07, 0.11, 0.12 or any value within the above range, and the present application does not limit this.
[0086] Among them, Ya and Yb below the above range cannot effectively protect the positive and negative electrodes of the battery, and Ya and Yb above the above range will deteriorate the battery performance. The range of M and N is limited based on business needs or experience values. If it is lower than the above range, the energy density of the battery cell will be reduced, and if it is higher than the above range, the energy density of the battery cell will be high, but the dynamic performance of the battery cell will be relatively poor.
[0087] Corresponding to the aforementioned application function realization method embodiment, the present application also provides an electrochemical device, an electronic device and corresponding embodiments.
[0088] An embodiment of the present application provides an electrochemical device, including a positive electrode sheet, a negative electrode sheet, a separator, and the aforementioned electrolyte.
[0089] The electrolyte includes a lithium salt, a non-aqueous organic solvent and an additive, and the additive includes a first additive and a second additive.
[0090] Preferably, the additive further comprises fluorocarbonate.
[0091] In the embodiment of the present application, the lithium salt is selected from at least one of an organic lithium salt or an inorganic lithium salt.
[0092] Preferably, the lithium salt is selected from at least one of compounds containing fluorine and lithium.
[0093] Preferably, the lithium salt is selected from at least one of hexafluorophosphate, hexafluoroarsenate, perchlorate, trifluorosulfonyl lithium, difluoro(trifluoromethylsulfonyl)imide lithium, tris(trifluoromethylsulfonyl)methyl lithium, and bis(trifluoromethylsulfonyl)imide lithium.
[0094] Preferably, the concentration of the lithium salt is 0.5 M to 1.5 M. If the lithium salt concentration is too low, the conductivity of the electrolyte is low, which will affect the rate and cycle performance of the entire battery system; if the lithium salt concentration is too high, the viscosity of the electrolyte is too high, which will also affect the rate of the entire battery system.
[0095] More preferably, the concentration of the lithium salt is 0.8M to 1.3M.
[0096] In the embodiment of the present application, the organic solvent is selected from at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl formate, ethyl formate, ethyl propionate, propyl propionate, methyl butyrate, and tetrahydrofuran.
[0097] In the embodiment of the present application, the positive electrode includes a positive electrode collector and a positive electrode active slurry layer located on the positive electrode collector, and the positive electrode active slurry layer includes a positive electrode active material; the negative electrode includes a negative electrode collector and a negative electrode active slurry layer located on the negative electrode collector, and the negative electrode active slurry layer includes a negative electrode active material.
[0098] The embodiments of the present application have no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.
[0099] In the embodiments of the present application, there is no particular restriction on the type of the positive electrode current collector, which can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. Preferably, the positive electrode current collector is a metal material.
[0100] Preferably, the positive electrode active material is one or more selected from lithium cobalt oxide LiCoO2, lithium nickel manganese cobalt ternary material, lithium iron phosphate LiFePO4, and lithium manganese oxide LiMn2O4.
[0101] More preferably, the positive electrode active material is selected from lithium nickel manganese cobalt ternary materials.
[0102] When lithium nickel manganese cobalt ternary material is selected as the positive electrode active material, it is more effective in improving the high temperature cycle performance of the battery compared to lithium cobalt oxide LiCoO2, lithium ferrous phosphate LiFePO4, and lithium manganese oxide LiMn2O4. This is because for nickel cobalt manganese oxide ternary materials, generally the higher the Ni content, the stronger the oxidizing property of the electrolyte. The synergistic effect of the first additive and the second additive in the embodiment of the present application can effectively inhibit the oxidation gas production effect of Ni in the ternary material on the electrolyte. Therefore, the first additive and the second additive have better compatibility with nickel cobalt manganese oxide ternary materials, and the performance improvement effect on the battery is more obvious.
[0103] Preferably, the negative electrode active material is selected from graphite and / or silicon, such as natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloys can be used as negative electrode active materials.
[0104] In one embodiment, the positive electrode active material layer further includes a conductive agent, a binder and a solvent.
[0105] In one embodiment, the conductive agent includes at least one of carbon materials such as natural graphite, artificial graphite, acetylene black, needle coke, carbon nanotubes, and graphene.
[0106] In one embodiment, the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose.
[0107] In the embodiments of the present application, there is no particular limitation on the material and shape of the diaphragm, as long as the effect of the present application is not significantly impaired.
[0108] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.
[0109] In some embodiments, the electrochemical device may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0110] In some embodiments, the outer packaging of the electrochemical device may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the electrochemical device may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0111] The present application has no particular limitation on the shape of the electrochemical device, which may be cylindrical, square, or any other shape.
[0112] An embodiment of the present application also provides an electronic device, comprising the aforementioned electrochemical device.
[0113] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0114] In order to further understand the present invention, the present application is described below in conjunction with embodiments. These embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.
[0115] 1. Preparation of batteries
[0116] (1) Preparation of electrolyte
[0117] EC / PC / EMC=2 / 1 / 7 mass ratio was mixed as an organic solvent. 3% of the additive FEC was added to the organic solvent and mixed evenly, and then LiPF6 was added to obtain a mixed solution with a LiPF6 concentration of 1.1 mol / L. The first additive and the second additive were added to the mixed solution according to the formula in Table 1 to prepare the electrolytes of various embodiments and comparative examples. Among them, FEC is fluoroethylene carbonate.
[0118] (2) Production of positive electrode:
[0119] The positive electrode active material, the conductive agent CNT, and the binder polyvinylidene fluoride are fully stirred and mixed in N-methylpyrrolidone solvent at a weight ratio of 97:1.5:1.5 to form a uniform positive electrode slurry. The slurry is coated on the positive electrode current collector Al foil, dried, and cold pressed to obtain a positive electrode sheet. The positive electrode active material is set according to Table 1.
[0120] (3) Production of negative electrode sheet:
[0121] The negative electrode active material graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are fully stirred and mixed in a proper amount of deionized water solvent at a mass ratio of 95:2:2:1 to form a uniform negative electrode slurry. The slurry is coated on the negative electrode current collector Cu foil, dried, and cold pressed to obtain a negative electrode sheet.
[0122] (4) Production of lithium-ion batteries:
[0123] Stack the positive electrode sheet, separator and negative electrode sheet in order, so that the separator is between the positive and negative electrodes to play an isolating role, and then wind it to the bare cell. Put the bare cell in the outer packaging bag, inject the electrolyte in Table 1 into the dried battery, and complete the preparation of the lithium-ion battery through vacuum packaging, static, formation, shaping and other processes.
[0124] Table 1 Recipe
[0125]
[0126]
[0127]
[0128]
[0129]
[0130] 2. Performance Test
[0131] (1) High temperature cycle test of batteries
[0132] Test method: Place the battery in a 45±2 degree environment, follow the standard charge and discharge cycle, cycle rate 1C, charging voltage 3.0-4.3V, and calculate the capacity retention rate of the battery after the cycle. The calculation formula is as follows:
[0133] The nth cycle capacity retention rate (%) = (nth cycle discharge capacity) / (first cycle discharge capacity)*100%.
[0134] (2) High temperature storage test of batteries:
[0135] Test method: Charge the divided battery cells to 4.3V at room temperature with a current of 0.5C, place the fully charged battery in an environment of 85 degrees for 12 hours, measure the thickness expansion rate by heat, and after returning to room temperature, discharge the battery cells to 3.0V with a current of 0.5C and record the discharge capacity.
[0136] The battery test results are shown in Table 2.
[0137] Table 2 Test results
[0138]
[0139]
[0140]
[0141] Combining the data in Table 1 and Table 2, by comparing Examples 1 to 8, it can be seen that as the content of the first additive increases, the high temperature cycle and storage performance of the battery improves accordingly. Further combined with Examples 9 to 12, and Examples 23 to 28, it can be seen that continuing to add the second additive can further improve the high temperature cycle and storage performance of the battery, indicating that the second additive and the first additive have a synergistic effect; further combined with Comparative Examples 4 and 5, it can be seen that further increasing the content of the first additive or the second additive will reduce the high temperature cycle and storage performance of the battery. This is because the content of the first additive or the second additive is too large, which will deteriorate the battery performance, and when 0.01≤Ya≤10, 0.01≤Yb≤5, the high temperature performance of the battery can be effectively improved; further, when 1≤Ya≤8, 0.5≤Yb≤3, the high temperature performance of the battery can be further effectively improved.
[0142] By comparing Example 10, Example 40 and Example 44, as well as Comparative Examples 6 and 7, it can be seen that when 0.01≤Ya≤10, 0.01≤Yb≤50, and 0.035≤M≤0.15, the high temperature performance of the battery can be improved while ensuring the battery energy density.
[0143] By comparing Example 10, Example 40 and Example 44, as well as Comparative Examples 6 and 7, it can be seen that when 0.01≤Ya≤10, 0.01≤Yb≤50, and 0.025≤N≤0.12, the high temperature performance of the battery can be improved while ensuring the battery energy density.
[0144] By comparing Examples 9 to 12 and Examples 20 to 48, it can be seen that when the first additive and the second additive satisfy 105≤(Ya+Yb) / (M*N)≤1200 with the positive and negative electrode material layers, the amounts of the first additive and the second additive can be adapted to the surface density of the positive electrode material layer and the negative electrode material layer to achieve effective protection of the positive and negative electrodes and enhance the high temperature cycle performance of the battery.
[0145] Further comparison of Examples 9 to 12 and Examples 20 to 39 shows that when the first additive and the second additive satisfy 200≤(Ya+Yb) / (M*N)≤1000 with the positive and negative electrode material layers, the amounts of the first additive and the second additive can be more matched to the surface density of the positive electrode material layer and the negative electrode material layer, so as to achieve more effective protection of the positive and negative electrodes and further improve the high temperature cycle performance of the battery.
[0146] By comparing Example 10, Example 49 to Example 51, it can be seen that when the positive electrode active material is selected from lithium nickel manganese cobalt ternary material, it is more effective in improving the high temperature cycle performance of the battery compared to lithium cobalt oxide LiCoO2, lithium ferrous phosphate LiFePO4, and lithium manganate LiMn2O4. This is because for nickel cobalt manganese oxide ternary materials, generally the higher the Ni content, the stronger the oxidizing property of the electrolyte. The synergistic effect of the first additive and the second additive in the embodiment of the present application can effectively inhibit the oxidation gas production effect of Ni in the ternary material on the electrolyte. Therefore, the first additive and the second additive have better compatibility with the nickel cobalt manganese oxide ternary material, and the performance improvement effect on the battery is more obvious.
[0147] 3. Battery EIS test
[0148] The lithium-ion batteries of Comparative Example 1, Comparative Example 3, Comparative Example 2, and Example 10 were selected, and the battery cells were adjusted to 50% SOC respectively. The electrochemical workstation was set with a disturbance voltage of 5 mV and a test frequency range of 0.04 Hz-100000 Hz. Three groups of tests were performed on each comparative example and example.
[0149] Test results such as Figure 1 As shown in the figure, Base-1#, Base-2#, and Base-3# represent three groups of test results for Comparative Example 1, Base+2%A-1#, Base+2%A-2#, and Base+2%A-3# represent three groups of test results for Comparative Example 3, Base+1%B-1#, Base+1%B-2#, and Base+1%B-3# represent three groups of test results for Comparative Example 2, and Base+2%A+1%B-1#, Base+2%A+1%B-2#, and Base+2%A+1%B-3# represent three groups of test results for Example 10.
[0150] By comparing Comparative Example 3 with Comparative Example 1, it is found that the addition of the first additive has a significant increase in the impedance of the battery, and by comparing Comparative Example 2 with Comparative Example 1, it is found that the addition of the second additive has a significant decrease in the impedance of the battery. By adding 2% of the first additive and 1% of the second additive at the same time, i.e., Example 10 and Comparative Example 1, due to the synergistic effect of the two, the second additive can largely balance the negative impact of the first additive on the impedance, achieving the effect of improving high temperature without significantly deteriorating the impedance.
[0151] Although the present application has been described with reference to preferred embodiments, it will be appreciated by those skilled in the art that various changes may be made and equivalents may be substituted for its elements without departing from the scope of the present application. In addition, many modifications may be made to adapt specific situations or materials to the teachings of the present application without departing from the substantive scope of the present application. Therefore, the present application is not intended to be limited to the specific embodiments disclosed as the best mode of implementing the present application contemplated, but the present application will include all embodiments falling within the scope of the appended claims.
[0152] All ranges disclosed in this application are inclusive of the endpoints, and the endpoints are combinable with each other.
[0153] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. An electrolyte, characterized in that: The invention comprises a first additive and a second additive, wherein the first additive comprises a nitrogen-containing heterocyclic acid anhydride compound, and the second additive comprises a borate compound, and the first additive and the second additive satisfy the following relationship with the positive and negative electrode material layers: 105≤(Ya+Yb) / (M*N)≤2000 The mass percentage of the first additive in the electrolyte is Ya%, the mass percentage of the second additive in the electrolyte is Yb%, and the mass of the positive electrode material layer per unit area on the positive electrode sheet is Mg / cm 2 , the mass of the negative electrode material layer per unit area on the negative electrode sheet is N g / cm 2 .
2. The electrolyte according to claim 1, characterized in that The first additive and the second additive satisfy the following relationship with the positive and negative electrode material layers: 200≤(Ya+Yb) / (M*N)≤1000.
3. The electrolyte according to claim 1, characterized in that The structural formula of the nitrogen-containing heterocyclic acid anhydride compound is as follows: In Formula 1, X1 is one of C and N atoms, X2 is a N atom, and R1 and R2 are each independently selected from a benzene ring, a cyano group, a halogen atom, a hydrogen atom, a C1-C10 alkyl group, a C1-C10 unsaturated alkyl group, a C1-C10 halogenated alkyl group, and a C1-C10 halogenated unsaturated alkyl group; preferably, R1 and R2 are each independently selected from a benzene ring, a cyano group, a halogen atom, a hydrogen atom, a C1-C3 alkyl group, a C1-C3 unsaturated alkyl group, a C1-C3 fluorinated alkyl group, and a C1-C10 fluorinated unsaturated alkyl group.
4. The electrolyte according to claim 3, characterized in that The first additive comprises at least one of the following nitrogen-containing heterocyclic acid anhydride compounds:
5. The electrolyte according to claim 1, characterized in that The structural formula of the borate ester compound is as follows: In formula 2, R3, R4, and R5 are each independently selected from one of a C1-C10 alkyl group, a C1-C10 unsaturated alkyl group, a C1-C10 fully halogenated or partially halogenated alkyl group, and a C1-C10 fully halogenated or partially halogenated unsaturated alkyl group; preferably, R3, R4, and R5 are each independently selected from one of a C1-C5 fully fluorinated or partially fluorinated alkyl group, and a C1-C5 fully fluorinated or partially fluorinated unsaturated alkyl group.
6. The electrolyte according to claim 5, characterized in that The second additive comprises at least one of the following borate compounds:
7. The electrolyte according to claim 1, characterized in that 0.01≤Ya≤10; and / or, 0.01≤Yb≤5; and / or, 0.035≤M≤0.15; and / or, 0.025≤N≤0.12; preferably, 1≤Ya≤8; and / or, 0.5≤Yb≤3.
8. An electrochemical device, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte as claimed in any one of claims 1 to 7.
9. The electrochemical device according to claim 8, characterized in that The positive electrode sheet includes a positive electrode current collector and a positive electrode active slurry layer located on at least one side of the positive electrode current collector, and the positive electrode active slurry layer includes a positive electrode active material; preferably, the positive electrode active material is selected from one or more of lithium cobalt oxide LiCoO2, lithium nickel manganese cobalt ternary material, lithium iron phosphate LiFePO4, and lithium manganese oxide LiMn2O4; further preferably, the positive electrode active material is selected from lithium nickel manganese cobalt ternary material.
10. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 8 or 9.
Citation Information
Patent Citations
Polycarbonyl nitrogen heterocyclic organic compound for organic cathode material of lithium battery and preparation method thereof
CN108711624A
Battery electrolyte additive, electrolyte containing additive and application of electrolyte
CN109638353A
Polycarbonyl hexaazabenzophenanthrene derivative type COF for water-based zinc ion battery positive electrode material and preparation method of polycarbonyl hexaazabenzophenanthrene derivative type COF
CN116425974A
Covalent organic framework material containing multiple oxidation-reduction active groups as well as preparation method and application of covalent organic framework material
CN117700738A
Non-aqueous electrolytic solution for lithium ion secondary cell
US20200099092A1